NFAM1 Promotes Pro-Inflammatory Cytokine Production in Mouse and Human Monocytes - Juchem, Kathryn W.; Gounder, Anshu P.; Gao, Jian Ping; Seccareccia, Elise; Yeddula, Narayana; Huffmaster, Nicholas J.; Côté-Martin, Alexandra; Fogal, Steven E.; Souza, Donald; Wang, Sarah Sirui; Glynn, Elizabeth R. A.; Yung, Ivy; et al. (Frontiers in Immunology, 2022)
NFAM1 is an ITAM bearing-transmembrane receptor that has been reported to play a role in B cell signaling and development. We performed expression analysis of NFAM1 using publicly available gene expression data sets and found that NFAM1 expression is significantly induced in intestinal biopsies from Crohn’s disease (CD) and ulcerative colitis (UC) patients. At the cellular level, we further observed high expression of NFAM1 in monocytes and neutrophils, in addition to expression in B and T cells. To explore the role of NFAM1 in multiple immune cells and its potential role in IBD, we generated NFAM1-/- mice. In contrast with previous reports using NFAM1-transgenic mice, NFAM1-/- mice have no obvious defects in immune cell development, or in T cell-dependent or T cell-independent B cell responses. Interestingly, NFAM1-/- monocytes produce reduced levels of TNF-α in response to activation by multiple IBD-relevant stimuli, including CD40L, TLR ligands and MDP. Additional cytokines and chemokines such as IL-6, IL-12, CCL3 and CCL4 are also reduced in CD40L stimulated NFAM1-/- monocytes. Collectively, these findings indicate that NFAM1 promotes pro-inflammatory monocyte development, thereby amplifying the response to diverse stimuli. Similarly, we observed that deletion of NFAM1 in human monocytes also reduced expression of CD40L-induced CCL4. Lastly, to assess the role of NFAM1 in IBD, we compared development of anti-CD40 induced colitis in NFAM1+/+ and NFAM1-/- mice. We found that although NFAM1 deletion had no impact on development of gut pathology, we did observe a decrease in serum TNF-α, confirming that NFAM1 promotes pro-inflammatory cytokine production in vivo. Taken together, we conclude that NFAM1 functions to amplify cytokine production, and should be further evaluated as a therapeutic target as part of a combinatorial regimen for treatment of autoimmune disease.